MULTI-ELEMENT DETERMINATION OF MACRO AND TRACE ELEMENTS IN KIDNEY OF DMBA AND LINALOOL APPLIED GUINEA PIGS BY INDUCTIVELY-COUPLED PLASMA ATOMIC EMISSION SPECTROMETRY (ICP-AES) - Ciftci, Harun; Dayangac, Alpaslan; Ozkaya, Ahmet; Cevrimli, Bekir S.; Erdag, Raziye; Olcucu, Ali; Ates, Sema (Parlar Scientific Publications (P S P), 2011)
Determination of trace elements in biological samples is important because of their vital role in metabolism, health and oxidative stress. Oxidative stress is caused by reactive oxygen species, depending on many factors in the etiology of various diseases. In our study, protective role of linalool (LIN), which has antioxidant properties in 7,12-dimethylbenz-[a]anthracene (DMBA), administered to guinea pigs was investigated in terms of some macro and trace elements, such as calcium, magnesium, copper, zinc, iron, cadmium and manganese. Determination of these elements in kidney was performed by inductively coupled plasma atomic emission spectrometry (ICP-AES) after microwave-assisted digestion method. Validation of the procedure was examined by using results of recovery experiments. The recovery values of the proposed procedure were found to be between 94.4-101.2%. As a result of the analysis, levels of calcium and cadmium in DMBA group increased when it was compared to control group (P<0.01), but was decreased when linalool was used with DMBA. Levels of magnesium, zinc and iron decreased in DMBA group in case of comparison with other groups (P<0.01), but increase was obtained in case of using linalool with DMBA. While copper levels between control and DMBA group were not significantly different (P>0.05), they increased in DMBA+LIN and LIN groups compared to control group (P<0.01). In addition, it was noted that the difference in the levels of manganese between groups was not significant (P>0.05). As a result, it can be concluded from the point of macro and trace elements that linalool is effective in the protection of kidney and some other important organs from oxidative stress.
Keywords: DMBA; 7,12-dimetilbenz-[a]antracene; linalool; trace element; ICP-AES; kidney; animal model